Serum 25(OH)D levels and mortality risk among middle-aged and elderly populations in the U.S.: A prospective cohort study - Yaowen Hu; Faliang Gao; Yuan Yang; Wei Yang; Huibo He; Jie Zhou; Yujie Zhao; Xi Chen; Wenyan Zhao; Xiaopeng He (PLoS ONE, 2025)
Objective To investigate the prevalence of vitamin D deficiency and its relationship with all-cause and cause-specific mortality among middle-aged and elderly populations in the U.S. Methods Data were sourced from the National Health and Nutrition Examination Survey (NHANES) 2001–2018. A total of 22,130 participants aged 40–70 years were included. Serum 25-hydroxy vitamin D [25(OH)D] concentrations were measured and categorized. The primary outcome was all-cause mortality, and secondary outcomes were cardiovascular disease (CVD) and cancer mortality. Multivariable-adjusted models and various statistical analyses were employed. Results The prevalence of vitamin D deficiency (≤50.00 nmol/L) was 33.59%, and insufficiency (≤75.00 nmol/L) was 71.74%. For all-cause mortality, the multivariate adjusted hazard ratios (HRs) across different 25(OH)D levels (< 25.00, 25.00–49.99, 50.00–74.99, and ≥ 75.00 nmol/L) were 1.00, 0.78 (0.65, 0.93) p = 0.0069, 0.59 (0.49,0.72) p < 0.0001, and 0.54 (0.44, 0.66) p < 0.0001 respectively. Similar patterns were observed for CVD mortality. There was no significant difference in cancer mortality between the moderately deficient and severely deficient groups, but lower mortality was found in the insufficient and sufficient groups compared to the severely deficient group. An L-shaped association between serum vitamin D levels and mortality was identified. Subgroup analyses were consistent with the main findings. Conclusion This study found that higher serum 25-hydroxyvitamin D concentrations are linked to lower all-cause, cardiovascular, and cancer mortality. The relationship is nonlinear: increases in concentration reduce death risk below a certain threshold, but above it, the association weakens. Further research is needed to understand causal mechanisms.